Beyond heteronormativity towards social justice: Disrupting gender operationalisation in teaching and learning trends in higher education - McDonald, Zahraa; Motala, Shireen (Critical Studies in Teaching and Learning, 2023)
Quantitative approaches, based on numerical analyses of operationalised variables, used to present teaching and learning trends in higher education, are pervasive. However, teaching and learning trends disaggregated by gender are generally collected and/or reported according to a binary operationalisation. The gender binary is associated with heteronormative dispositions. This paper examines the extent to which gender operationalisation, as it relates specifically to teaching and learning trends in South Africa, promotes heteronormative dispositions and the consequent implications for social justice. Framed within Nancy Fraser’s approach to social justice, heteronormative dispositions constitute misrecognition and hence injustice. Based on a review of data gathering and reporting on teaching and learning trends by the Department of Higher Education and Training (DHET), it is clear that, at present, non-binary expressions or analyses of gender are misrecognised. The paper argues that gender operationalisation associated with trends in teaching and learning contributes to heteronormative dispositions that are not commensurate with social justice. It calls for the disruption of binary gender operationalisation linked to teaching and learning trends as a mechanism for full recognition and socially just knowledge production. This paper does not focus on research in a moment of social disruption but rather seeks to disrupt research processes which could be exclusionary and promote injustice, and thus interrupt socially-unjust representations, specifically as it relates to gender.